2017
DOI: 10.1177/1078390317712598
|View full text |Cite
|
Sign up to set email alerts
|

Professionals’ Awareness of Sexual Abuse in Late Life: An Exploratory Survey

Abstract: This exploratory survey indicates that professionals are partially aware of the existence of and the need to address the ESA phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Although this relatively low rate may suggest that the phenomenon is scarce, it may also indicate barriers to detecting SAWLL and practitioners’ lack of awareness (Alon et al, 2018; Goldblatt et al, 2020). These barriers may be manifested by older women’s difficulty in reporting sexual assault due to physical and cognitive deterioration (e.g., Bows, 2018; Fileborn, 2017), as well as dependency relationships, when the offender is a family member or a caregiver (Mann et al, 2014).…”
Section: Sawllmentioning
confidence: 93%
“…Although this relatively low rate may suggest that the phenomenon is scarce, it may also indicate barriers to detecting SAWLL and practitioners’ lack of awareness (Alon et al, 2018; Goldblatt et al, 2020). These barriers may be manifested by older women’s difficulty in reporting sexual assault due to physical and cognitive deterioration (e.g., Bows, 2018; Fileborn, 2017), as well as dependency relationships, when the offender is a family member or a caregiver (Mann et al, 2014).…”
Section: Sawllmentioning
confidence: 93%
“…This can include frustration, isolation, apprehension and depression (Alon et al, 2018), yet risks for depression are decreased with greater social support (Melchiorre et al, 2016). Common responses also include anxiety, passive or hostile behavior, insomnia, posttraumatic stress (Bows, 2018b), changes in self-image, limited trust, and problems with maintaining control over daily life (Alon et al, 2018). Gerino et al (2018) have also reported that IPV in later life has been linked with strong emotions, such as increased feelings of worthlessness and the loss of one's own identity.…”
Section: Health-related Consequences Of Sexual Violence In Later Lifementioning
confidence: 99%
“…As Brozowski and Hall (2010) have summarized, individuals who are generally vulnerable to oppression, such as women and members of nondominant populations, experience compounded prejudice as they grow older, which increases risks for violence, including sexual violence. Dynamics of power and vulnerability relating to age, gender, race and other characteristics that place individuals at a greater risk for structural oppression and violence (including SV) have been well established (Alon et al, 2018; Bows, 2018a; Gerino et al, 2018). Referrals have also most often been requested due to physical symptoms, genital trauma is more common in later life, and older women are more often alone at home or in facilities and disabled (Eckert & Sugar, 2008).…”
Section: Prevalence Of Sexual Violence In Later Life and Impacts On H...mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be argued that SAWLL’s low frequency indicates the phenomenon’s scarcity. However, researchers indicate a more complex picture, related to professionals’ partial awareness of this phenomenon (Alon et al, 2018; Fileborn & Barrett, 2019). In addition, clinical evidence shows that older women are actively being harmed, punished, and threatened in response to disclosing sexual assault, described as Cascading victimization, which occurs “when one or more episodes of abuse trigger subsequent, additional forms of abuse inflicted by the same or other offender(s)” (Ramsey-Klawsnik & Miller, 2017, p. 345).…”
mentioning
confidence: 99%